An empirical study of how the Dutch healthcare regulator first formulates the concept of trust and then puts it into practice - Sandra Spronk; Annemiek Stoopendaal; Paul B. M. Robben (BMC, 2019)
Abstract Background Responsive regulation assumes that the parties being regulated are trustworthy and motivated by social responsibility. This assumes that regulation based upon trust will improve the regulated organization more effectively than other regulation models. The purpose of our qualitative study was to unravel the most important elements of trust in the inspectee which can support the inspector's work and to develop a model and a framework of trust that can be used by the inspectors to legitimize their trust in the inspectee. Methods We conducted an empirical study on trust regarding the regulation of care services to reveal how trust in the inspectee is conceptualized and assessed. Based on literature and empirical research, we synthesized the concept of trust into six elements, five regarding behavior, and a sixth looking at information about its context. We developed a practical framework for the concept to reduce the conceptual ambiguity, strengthen regulatory assessment, and support appropriate tailoring of the regulatory response. Results Six elements with respect to trust emerged from the data: showing integrity; transparency; ability to learn; accepting feedback; showing actual change in behavior; context information. These five behavioral elements, plus the context information were merged into a Framework of Trust and designed into an interactive PDF document. Conclusions This study has sought to address a gap in the empirical knowledge regarding the assessment of trust in the inspectee. The results aim to inform and clarify the regulatory conceptualization and understanding of trust in the inspectee. Other inspectorates may learn from these results for their own practice and explore whether operational deployment of our Framework of Trust effects their assessment and enforcement strategies.